The interpretation of the New Testament 1861-1986 - Neill, Stephen, 1899-1984; Wright, Tom; Firth lectures, 1962. (Oxford, NY Oxford UP, 1988)
Includes index.
Keywords: Bible. N.T. -- criticism, interpretation, etc. -- history -- 19th century; Bible. N.T. -- criticism, interpretation, etc. -- history -- 20th century